Development of Students’ Satisfaction Scale - Jamshid Ghasemi (The Journal of Quality in Education)
The present study aimed to investigate the factors, features, and variables that might affect EFL students’ satisfaction. Despite the importance of this concept, no validated instrument was found to measure these constructs. To fill the gap, this study developed and validated a scale of EFL students’ satisfaction. A 41-item questionnaire was developed and administered to 305 EFL students (171 females and 134 males). We ran Structural Equation Modeling (SEM) to analyze the collected data and test the path model of the study. The reliability and validity of the questionnaires were estimated using exploratory and confirmatory factor analyses. The results indicated acceptable goodness of fit indices (Chi-squared=1/779, p < .001, CFI = 0.947, TLI = 0.908, RMSEA= 0.048, SRMR = 0.043, AIC =16650 and BIC =17140). The findings of the study further showed that EFL students’ satisfaction was highly sensitive to some of the subscales of the study and that under certain conditions often as the result of interplay between the components of the scale, the professional perceptions of the participants undergo severe changes. The findings of this study have implications for researchers, as well as language teachers and other practitioners in the field of education and teaching quality.